Late Nonanastomotic Pseudoaneurysm From the Prosthetic Graft: A Successful Transcatheter Arterial Embolization Using Coils. (April 2021) - Saiga, Atsushi; Hashiba, Jun; Koizumi, Jun; Ueda, Hideki; Kubota, Yoshihiro; Wada, Takeshi; Akutsu, Akira; Uno, Takashi
A 71-year-old man who received a total arch replacement with a knitted Dacron® graft presented aneurysmal sac re-expansion due to leakage at the distal anastomotic site of the graft. He did not tolerate the stress of general anesthesia due to severe pulmonary function impairment. Therefore, thoracic endovascular aortic repair (TEVAR) in zone 3 was performed under epidural anesthesia. Contrast-enhanced computed tomography (CT) revealed another leakage into the aneurysmal sac in zone 1 after performing TEVAR. Because open surgical repair and debranching TEVAR were contraindicated, transcatheter arterial embolization was performed with careful consideration of his comorbidities. Follow-up contrast-enhanced CT performed 2 weeks after embolization indicated no opacification of the aneurysmal sac, and noncontrast-enhanced CT a year after embolization showed no dilatation of the aneurysmal sac.